2017
DOI: 10.1371/journal.pone.0170541
|View full text |Cite|
|
Sign up to set email alerts
|

The evolution of cost-efficiency in neural networks during recovery from traumatic brain injury

Abstract: A somewhat perplexing finding in the systems neuroscience has been the observation that physical injury to neural systems may result in enhanced functional connectivity (i.e., hyperconnectivity) relative to the typical network response. The consequences of local or global enhancement of functional connectivity remain uncertain and this is particularly true for the overall metabolic cost of the network. We examine the hyperconnectivity hypothesis in a sample of 14 individuals with TBI with data collected at app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
55
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 72 publications
11
55
1
Order By: Relevance
“…Cassidy and colleagues (2018) recently demonstrated that persistent homology, a technique from topological analysis, has the potential to quantify the similarity of individual functional connectomes across different parcellations. We believe that such directions hold promise for supporting reproducible findings in clinical RSFC studies (Craddock, James, Holtzheimer, Hu, & Mayberg, 2012;Roy et al, 2017;Schaefer et al, in press).…”
Section: Creating Comparable Network In Clinical Samplesmentioning
confidence: 72%
“…Cassidy and colleagues (2018) recently demonstrated that persistent homology, a technique from topological analysis, has the potential to quantify the similarity of individual functional connectomes across different parcellations. We believe that such directions hold promise for supporting reproducible findings in clinical RSFC studies (Craddock, James, Holtzheimer, Hu, & Mayberg, 2012;Roy et al, 2017;Schaefer et al, in press).…”
Section: Creating Comparable Network In Clinical Samplesmentioning
confidence: 72%
“…The loss of nodal specificity may result in incorporation of additional resources or engagement of alternative auxiliary pathways [ 24 , 66 ] or hubs (see Fig 10 in TBI) resulting in less freedom for expression of network dynamics and greater susceptibility to neural noise [ 64 ]. This “hyperconnectivity” response observed in other samples [ 5 , 14 , 53 , 67 ] may operate to accommodate ongoing task demands in the context of reduced neural resources, but one consequence may be reduced network flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with Roy and colleagues [ 53 ], we define the cost of each functional edge as the product of the Euclidean distance between the ROI-pair it connects and the absolute weight of the connection. The overall network cost is determined as the total cost for all edges within the network.…”
Section: Methodsmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] For example, a TBI disrupts the optimal balance between network integration and segregation, 8,9 modular organization, 6,10 and the efficiency of brain communication. 7,8,11,12 Neuroimaging tools have also provided evidence for training-dependent neuroplasticity in healthy adults. [13][14][15] Accordingly, the neurorehabilitation community seeks to identify training-induced neuroplasticity of the injured brain.…”
Section: Introductionmentioning
confidence: 99%
“…Although our previous studies [18][19][20][21] and those of others 22,23 demonstrated neuroplasticity after cognitive training in TBI, little is known about training-induced changes in the full-scale organization of the brain networks in individuals with TBI. Because the assessments of whole-brain networks in TBI utilizing rsfMRI and graph theory have provided insights into the brain systems disrupted by DAI, 3,5,6,[8][9][10][11][12] it would be informative to identify training-related neuroplasticity in TBI at the whole-brain level. Furthermore, assessing training-dependent plasticity of the network at the whole-brain level is advantageous, given that cognitive training is often multifaceted and addresses heterogeneous and complex patterns of cognitive dysfunction in TBI.…”
Section: Introductionmentioning
confidence: 99%